Psychosocial Experiences and Challenges of Pregnant Teenagers in GA South Municipality - Mawutor, Courage Jerry Worlanyo; Setsoafia, Rejoice Ama (Journal of Advanced Psychology, 2023)
Purpose: The purpose of this study is to explore the psychosocial challenges of pregnant teenagers in Ga South Municipality. The specific objectives were to: explore the nature of teenage pregnancies, assess psychological challenges affecting pregnant teenagers, assess social challenges of pregnant teenagers and suggest counselling interventions that can ameliorate identified challenges. Methodology: The research design used in this study was qualitative because the study aimed to understand the psychosocial experiences of teenage mothers in schools. The study used a purposive sampling method which is an example of non-probability sampling technique. Pregnant teenagers between ages 10-19 were recruited and in-depth interview (IDI) was carried out. The IDI was chosen because it gives more information on sensitive issues. Data processing and analysis started on the day of the in-depth interview. Findings: The study revealed that multiple factors contribute to the high levels of teenage pregnancy in the Ga South Municipality and most pregnant teenagers go through a lot of psychosocial challenges. The results and findings show that the canker of teenage pregnancy requires a multi-faceted approach at both structural and individual levels to tackle the challenge. Furthermore, poverty and low levels of living conditions in rural areas contributed greatly to high incidence of teenage pregnancy as observed in Ga South Municipality Area. It is recommended that; Ghana Education Service will need to revise its curriculum and enable teachers enhance their knowledge and skills in teenage sexual health and values clarification sessions. Unique Contribution to Theory, Policy and Practice: Churches and other religious bodies should educate their members about the effects of teenage pregnancy and its impacts on children through counseling and also plan for activities that mostly involve marriage couples.